EVALUASI KONSEP PENDIDIKAN PANCASILA DALAM KONTEKS GLOBALISASI: PERSPEKTIF FILOSOFIS DAN PENDIDIKAN - Wahyu Dodi Rifai (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Pancasila education, as the fundamental principle and ideology of the Indonesian nation, plays a central role in character-building, especially amidst the rapidly advancing globalization. Globalization has significantly impacted local values, including the education system, which increasingly prioritizes global competencies and international standards. This study aims to evaluate the relevance and implementation of Pancasila education in the context of globalization by examining changes in curriculum, the influence of foreign cultures, and the challenges in applying Pancasila education in the digital era. The research method uses a descriptive qualitative approach with literature review, analyzing various written sources related to Pancasila education, globalization, and its impact on national character. The findings reveal that although the values of Pancasila remain relevant in character-building, Pancasila education faces significant challenges due to shifts in cultural values and priorities within the educational curriculum. Pancasila education needs to be integrated with more innovative approaches, utilizing technology, and aligning with the demands of globalization while preserving its local essence. The recommendations emphasize the need for educators to enhance their role in instilling Pancasila values through methods that are adaptive and relevant to contemporary developments. This study contributes to the development of Pancasila education theory in the context of globalization and serves as an important reference for educational policies in Indonesia.